If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -5x = 12x Solving 4 + -5x = 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 4 + -5x + -12x = 12x + -12x Combine like terms: -5x + -12x = -17x 4 + -17x = 12x + -12x Combine like terms: 12x + -12x = 0 4 + -17x = 0 Add '-4' to each side of the equation. 4 + -4 + -17x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -17x = 0 + -4 -17x = 0 + -4 Combine like terms: 0 + -4 = -4 -17x = -4 Divide each side by '-17'. x = 0.2352941176 Simplifying x = 0.2352941176
| 5x+90=7X | | 18x-2=92 | | 9z-11-11z=5z-14-7z | | x^2+5x+8=3(x^2-x)-4 | | p/2-1/5=2-p/3 | | 18x=94 | | 32(x-1)+115x+11(x+3)=1607 | | 32(x-1)+115x+2(x+3)=1607 | | 10t-3=2 | | 10x+4=56 | | 15-2z=7 | | 45g=-7 | | -7=45g | | 5x-2=82 | | x^3-x-90x^2+90=0 | | x^3-x=90*(x^2-1) | | 5x+20=85 | | 2ix^2+5x+2i=0 | | 120*12= | | -6a+10=-3 | | x^2-22x+11=0 | | 16x=y+80 | | 9i*10i=x | | x^3-90x^2-5x+90=0 | | X^3-90*x^2-2*x+87=0 | | x^4-x^3-5x^2+3x+2= | | 0.5x+20=50 | | X^3+90*x^2-2*x+87=0 | | 8n-12=-12m+8 | | 6x+4=7x+4 | | 11-3x=9-7x | | x^3+4x^2+x-6= |